Parenting Of Single Parent Children In An Effort To Shape Children's Behavior - Ira Rahmawati; Ahmad Junaidi; Busriyanti Busriyanti (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The high divorce rate in Jember is a major problem in the biological and psychological development of a child. In this case the author wants to explore the parenting patterns of divorced families, both those who still maintain good communication between the three (husband-child-wife) and vice versa. There are several parenting patterns that parents can use. The author wants to try to know and describe the parenting patterns of single parents in an effort to shape children's behavior. The results of this study are presented descriptively through a qualitative approach in order to obtain clear information about the focus of the problem. The results of this study can be concluded, namely first, democratic parenting is the parenting of parents who interact with their children using how to provide freedom with supervision and second, permissive parenting is a parenting pattern where parental attention is valued less towards children or children always get whatever they want without control and limits